HISTORY OF SCIENCE: Muslim inventions that shaped the modern world By Olivia Sterns for CNN - Haque, Anwar Ul (International Journal of Pathology, 2021)
In 9th century Spain, Muslim inventor Abbas ibn Firnas designed a flying machine – hundreds of years before da Vinci drew plans of his own. STORY HIGHLIGHTS Exhibition celebrates 1,000 years of "forgotten" Muslim heritage From coffee to cranks, items we couldn’t live without today are Muslim inventions Modern hospitals and universities both began in 9th century North Africa London, England (CNN) – Think of the origins of that staple of modern life, the cup of coffee, and Italy often springs to mind. But in fact, Yemen is where the ubiquitous brew has its true origins. Along with the first university, and even the toothbrush, it is among surprising Muslim inventions that have shaped the world we live in today. The origins of these fundamental ideas and objects – the basis of everything from the bicycle to musical scales – are the focus of "1001 Inventions," a book celebrating "the forgotten" history of 1,000 years of Muslim heritage. "There’s a hole in our knowledge, we leap frog from the Renaissance to the Greeks," professor Salim al-Hassani, Chairman of the Foundation for Science, Technology and Civilization, and editor of the book told CNN.